1995
DOI: 10.1159/000126868
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Hypothalamic Lesions Inhibit Corticosteroid Feedback Regulation of Basal ACTH during the Trough of the Circadian Rhythm

Abstract: We have determined the effects of bilateral electrolytic lesions of the ventromedial hypothalamus (VMH) on activity in the hypothalamo-pituitary-adrenal (HPA) system. Acutely, during the first 5 days, lesions of the anterior-medial VMH caused loss of the diurnal rhythms in food intake and plasma corticosterone (B) levels. Plasma B concentrations were elevated during the time of the normal trough of the basal diurnal rhythm in HPA axis activity and the diurnal rhythm in food intake was abolished, in agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 35 publications
(51 reference statements)
5
23
0
Order By: Relevance
“…Thus, altered maternal sensory input (e.g. licking and grooming) was found to influence CRH-CRF 2 signaling in the hypothalamic ventromedial nucleus (25), a region shown previously to regulate stressrelated PVN function (48,49). Further evidence for modulation of CRH expression in structures comprising this sensory integration pathway (e.g.…”
Section: How Do Sensory Signals Resulting From Early-life Handling Almentioning
confidence: 63%
“…Thus, altered maternal sensory input (e.g. licking and grooming) was found to influence CRH-CRF 2 signaling in the hypothalamic ventromedial nucleus (25), a region shown previously to regulate stressrelated PVN function (48,49). Further evidence for modulation of CRH expression in structures comprising this sensory integration pathway (e.g.…”
Section: How Do Sensory Signals Resulting From Early-life Handling Almentioning
confidence: 63%
“…Contrary to the corticosterone data, ACTH levels showed no diurnal variation during the different Ringer's infusions ( p Ͼ 0.5), although variability during the CT10 experiment was considerably higher than at any other time of the day (16.8 Ϯ 2.8 vs 6.8 Ϯ 1.9, 7.6 Ϯ 2.3, 10.6 Ϯ 1.1, and 11.0 Ϯ 2.4 pg/ml). A number of previous studies have reported diurnal variations in plasma ACTH levels Carnes et al, 1989;Bagdy et al, 1991;Kwak et al, 1992;Ixart et al, 1993), but quite a few others failed to detect significant diurnal variations (Wilkinson et al, 1979;Akana et al, 1986;Carnes et al, 1986;Cascio et al, 1987;Kwak et al, 1993;Suemaru et al, 1995). Important factors that may contribute to the difficulty of finding a circadian ACTH rhythm are the low amplitude of the rhythm, the episodic secretion of ACTH, the sampling protocol used (Carnes et al, 1986;Turek and Van Cauter, 1988;Carnes et al, 1989), and the assay variability (e.g., CT times in different assays).…”
Section: Discussionmentioning
confidence: 99%
“…The VMH is also a key structure in the complex coordination of diurnal variation in the hypothalamic-pituitary-adrenal (HPA) axis tone [41] VMH lesions disrupt a number of functions including the circadian rhythms of food intake, insulin secretion and adrenocortical function [13]. A key mechanism by which the VMH mediates signals inhibiting the HPA axis is via occupancy of mineralocorticoid receptors on VMH neurons [41].…”
Section: Discussionmentioning
confidence: 99%
“…A key mechanism by which the VMH mediates signals inhibiting the HPA axis is via occupancy of mineralocorticoid receptors on VMH neurons [41]. However, a role for activation of CRF 2 receptors in modulating some aspects of the diurnal cycle of the HPA axis tone cannot be excluded [12].…”
Section: Discussionmentioning
confidence: 99%